Negative rates, monetary policy transmission and cross-border lending via international financial centres - Desislava éC. Andreeva; Andra Coman; Mary Everett; Maren Froemel; Kelvin Ho; Simon Lloyd; Baptiste Meunier; Justine Pedrono; Dennis Reinhardt; Andrew Wong; Eric Wong; Dawid çZochowski (European Central Bank (ECB), 2023)
We study the effects of negative interest rate policies (NIRP) on the transmission of monetary policy through cross-border lending. Using bank-level data from international financial centres - the United Kingdom, Hong Kong and Ireland - we examine how NIRP in the economies where banks have their headquarters influences cross-border lending from financial-centre affiliates. We find that NIRP impairs the bank-lending channel for cross-border lending to non-bank sectors, especially for those banks that have only a weak deposit base in IFCs - and are thus relatively more exposed to NIRP in their headquarters. Using euro-area data, including bank-level data from France, we find that NIRP does not influence overall cross-border lending from banks' headquarters' economies, but NIRP does impair lending to financial sectors based in IFCs. This impairment is stronger for banks with a large deposit base in headquarter economies exposed to NIRP.
Keywords: E52; F34; F36; F42; G21; 330; Bank lending; Cross-border lending; International financial centres; Monetary policy; Negative interest rates; Risk-taking